Damped perturbations in stellar systems: genuine modes and Landau-damped waves. Issue 1 (24th February 2021) - Polyachenko, E V; Shukhman, I G; Borodina, O I
ABSTRACT: This research was stimulated by the recent studies of damping solutions in dynamically stable spherical stellar systems. Using the simplest model of the homogeneous stellar medium, we discuss non-trivial features of stellar systems. Taking them into account will make it possible to correctly interpret the results obtained earlier and will help to set up decisive numerical experiments in the future. In particular, we compare the initial value problem versus the eigenvalue problem. It turns out that in the unstable regime, the Landau-damped waves can be represented as a superposition of van Kampen modes plus a discrete damped mode, usually ignored in the stability study. This mode is a solution complex conjugate to the unstable Jeans mode. In contrast, the Landau-damped waves are not genuine modes: in modes, eigenfunctions depend on time as exp (−iω t ), while the waves do not have eigenfunctions on the real $v$ -axis at all. However, 'eigenfunctions' on the complex $v$ -contours do exist. Deviations from the Landau damping are common and can be due to singularities or cut-off of the initial perturbation above some fixed value in the velocity space.